The monetary policy decision-making process and the term structure of interest rates - Hans Dillén (Sveriges Riksbank, 2008)
This paper presents a theoretical model of the term structure of interest rates based on the monetary policy decision-making process at modern central banks. Evaluations of explicit expressions for the spot and forward rate curve render several important results: (i) Spot and forward rates are explicit functions of the number of policy meetings during the time to maturity rather than the time to maturity itself. Consequently, the forward rate curve is step-shaped. (ii) In addition, there are calendar time effects, i.e. the position within the policy cycle is also of importance, especially for short term interest rates. (iii) The forward rate curve exhibits hump-shaped responses to economic shocks and a modified version of the Nelson-Siegel model can be obtained as a special case.
Keywords: G12; E43; E52; 330; the term structure of interest rates; interest rate stepping; policy gap; calendar time effects; hump-shaped responses; Geldpolitik; Zins; Zeit; Zinsstruktur; Theorie